Quantitative assessment of renal functions using 68Ga-EDTA dynamic PET imaging in renal injury in mice of different origins - Ding, Ying; Liu, Yu; Zhang, Li; Deng, Yinqian; Chen, Huanyu; Lan, Xiaoli; Jiang, Dawei; Cao, Wei (Frontiers in Medicine, 2023)
Background Early detection of kidney diseases can be challenging as conventional methods such as blood tests or imaging techniques (computed tomography (CT), magnetic resonance imaging (MRI), or ultrasonography) may be insufficient to assess renal function. A single-photon emission CT (SPECT) renal scan provides a means of measuring glomerular filtration rates (GFRs), but its diagnostic accuracy is limited due to its planar imaging modality and semi-quantification property. In this study, we aimed to improve the accuracy of GFR measurement by preparing a positron emission tonometry (PET) tracer 68Ga-Ethylenediaminetetraacetic acid (68Ga-EDTA) and comprehensively evaluating its performance in healthy mice and murine models of renal dysfunction. Methods Dynamic PET scans were performed in healthy C57BL/6 mice and in models of renal injury, including acute kidney injury (AKI) and unilateral ureter obstruction (UUO) using 68Ga-EDTA. In a 30-min dynamic scan, PET images and time-activity curves (TACs) were acquired. Renal function and GFR values were measured using renograms and validated through serum renal function parameters, biodistribution results, and pathological staining. Results 68Ga-EDTA dynamic PET imaging quantitatively captured the tracer elimination process. The calculated GFR values were 0.25 ± 0.02 ml/min in healthy mice, 0.01 ± 0.00 ml/min in AKI mice, and 0.25 ± 0.04, 0.29 ± 0.03 and 0.24 ± 0.01 ml/min in UUO mice, respectively. Furthermore, 68Ga-EDTA dynamic PET imaging and GFRPET were able to differentiate mild renal impairment before serum parameters indicated any changes. Conclusions Our findings demonstrate that 68Ga-EDTA dynamic PET provides a reliable and precise means of evaluating renal function in two murine models of renal injury. These results hold promise for the widespread clinical application of 68Ga-EDTA dynamic PET in the near future.